Diurnal pastoralism does not reduce juvenile recruitment nor elevate allostatic load in spotted hyenas. Issue 11 (5th October 2022) - Dheer, Arjun; Davidian, Eve; Courtiol, Alexandre; Bailey, Liam D.; Wauters, Jella; Naman, Philemon; Shayo, Victoria; Höner, Oliver P.
Abstract: Anthropogenic activity can have substantial effects on wildlife. These effects may vary according to the characteristics of the activity and the species involved. Although effects on behaviour are well studied, studies of effects on fitness and physiology are scarce, particularly for group‐living species. We exploited a natural experimental setup to investigate the effect of diurnal pastoralism on juvenile recruitment and allostatic load in a population of free‐ranging spotted hyenas in the Ngorongoro Crater, Tanzania, over a 24‐year period. Pastoralism was restricted to the territories of two of the eight study clans, allowing us to compare juvenile recruitment in exposed and unexposed clans. We also compared faecal glucocorticoid metabolite concentrations (fGMC)—a biomarker of an organism's allostatic load—between exposed and unexposed clans using 975 faecal samples from 475 hyenas. We found no detectable difference in juvenile recruitment nor fGMC between the exposed and unexposed clans, indicating that the pastoralism had no substantial deleterious effect on the spotted hyenas. The lack of a deleterious effect likely stems from the combined effect of the predictable and undisruptive nature of the pastoralism, the socio‐ecology of spotted hyenas and the Ngorongoro Crater's consistently abundant prey. Our findings demonstrate that exposure to anthropogenic activity may be compatible with the persistence of certain group‐living species, especially if the overlap between the species' critical behaviours and the activity is limited. Our study thereby provides new perspectives for ecologists, conservation biologists and stakeholders who seek to assess human–wildlife conflicts and balance the needs of local human communities and wildlife. Abstract : This study emphasizes the importance of interpreting the impact of anthropogenic activity in light of the socio‐ecology of the species of conservation interest. By measuring reproductive performance in terms of recruitment at the level of groups, the work offers a new perspective on the study of human–wildlife conflict. Muhtasari: Shughuli za kibinadamu zinaweza kuwa na athari kubwa kwa wanyamapori. Athari hizi huweza kutofautiana kutokana na aina ya shughuli na tabia ya wanyamapori husika. Ingawa athari za kitabia zimetafitiwa vizuri, tafiti katika utimamu wa mwili na fiziolojia ni chache hasa katika spishi zinazoishi katika makundi. Tulifanya majaribio kuchunguza athari za ufugaji wa kila siku katika ukuaji wa watoto na athari za mkazo kwa idadi ya fisi madoa doa huru katika eneo la Kreta ya Ngorongoro kwa kipindi cha miaka 24. Ufugaji katika eneo la Kreta ulidhibitiwa kuwa katika mipaka ya koo mbili tu kati ya nane za kitafiti, hivyo kuturuhusu kulinganisha ukuaji wa watoto kati ya koo ambazo ufugaji ulifikia na zile ambazo ufugaji haukuathiri. Vile vile, tulilinganisha kiwango cha metabolite ya glukokotikoidi katika kinyeshi (fGMC), ambacho ni kiashiria cha mkazo kwa wanyama kati ya koo zilizofikiwa na ufugaji na zile ambazo hazikufikiwa kwa kutumia sampuli 975 za kinyesi kutoka kwa fisi madoa 475. Hatukupata tofauti ya wazi katika ukuaji wa watoto na mkazo kati ya koo zilizofikiwa na zile ambazo hazikufikiwa na ufugaji kuonyesha kuwa ufugaji haukuwa na athari hasi kwa fisi madoa. Kukosekana kwa athari hasi pengine kunatokana na athari mjumuiko za asili ya ufugaji kunakotabirika na usio na usumbufu, ikilojia‐jamii ya fisi madoa na uthabiti wa idadi kubwa ya mawindo ndani ya Kreta. Matokeo ya utafiti wetu unaonesha kuwa, shughuli za kibinadamu zinaweza kuendana na kustahilimiliwa na aina fulani ya spishi zinazoishi katika makundi, hasa ikiwa muingiliano kati ya spishi na shughuli utadhibitiwa. Kwa hivyo, utafiti wetu unatoa mitizamo mipya kwa wana ikolojia, wana biolojia wa uhifadhi na washikadau katika kutathmini migogoro ya binadamu na wanyama na kuleta usawa kati ya mahitaji ya jamii za wanadamu na wanyamapori.